PENDAMPINGAN DAN PELATIHAN PENGGUNAAN SMART VILLAGE GUNA MENINGKATKAN PELAYANAN DESA DI PEKON SUKANEGERI JAYA - Heni Sulistiani; Agung Saputra; Auliya Rahman Isnain; Dedi Darwis; Yuri Rahmanto; Aprian Nuriansah; Aidil Akbar (Universitas Teknokrat Indonesia, 2022)
Technological developments require all parties to be able to apply it in all fields. The village government must also apply information technology in managing its administrative activities and in terms of village services. For this reason, it is necessary to develop a smart village application for villages that want to progress. This service activity aims to provide assistance and training on the use of smart villages for the community and village officials in Pekon Sukanegeri Jaya. Pekon Sukanegeri Jaya already has a smart village application that is ready to be implemented for the community and village officials. The village office has also been equipped with wifi or a smooth internet network, so that it can be used by the community and village officials to implement the smart village application. However, the community and village officials have not fully understood and implemented smart villages in their work. Therefore, the service team needs to provide assistance and training on the use of smart villages for the community and village officials. With this service activity, it is hoped that it can improve the ability of the community and village officials to use the smart village application and there will be an increase in village office services